Penguatan Nilai Toleransi Melalui Budaya Sekolah di SMK Plus 2 Mei - Widianto; Fitri Mutmainnah (PT FORMOSA CENDEKIA GLOBAL, 2022)
Tolerant behavior fluctuates, which can have a negative impact so we need to be careful. This is because the impact that appears is detrimental. As one of the nation's moral builders, education is responsible for shaping tolerant behavior through school culture. This study aims to determine the characteristics of school culture and strengthening the value of tolerance through school culture. This research is a qualitative research using a phenomenological approach. Data collection techniques using observation, interviews, and documentation. The research sample consisted of principals, vice principals, teachers, and students. The school culture at Vocational High School Plus 2 May strengthens the value of tolerance through a positive climate, where schools pay attention to several things including the availability and arrangement of facilities and infrastructure, school values ​​are used as standards of action, and shared assumptions from school members.